Art and technology: an analysis of this relationship in the field of graphic art since 1960, with specific emphasis on the development of printmaking - Thorburn, Dominic (Rhodes University, Faculty of Humanities, Department of Fine Art, 1984)
From Introduction: The reIationship between technology and art today is a logical extension of a collaborative tradition with ancient roots. The artist has always been a principal perpetrator of technological innovation. He, through the natural progression of technical means, has virtually evolved each new art form. There are many examples such as the 'lost wax' casting process, Jan Van Eycks oil paint innovations, Senefelders 'chemical printing' and Niecephore Niepce's first eight hour photographic exposures. Even woodblocks were in their time an innovation. All art uses technology of a kind and artists who prefer to remain aloof from it are in fact merely using technologies absorbed in older traditional media further back in the history of art. It is the flexibility of art to adapt to changing conditions of the world today which has spurred change and brought about a new dynamism in the graphic arts. The present intensity of interest in the print can be directly attributed to the advancement of technology and communication in this century. A whole new field of materials, methods and techniques are now available to the venturesome graphic artist and printmaker. Along with the contemporary technology dedication to expression leads naturally to innovation in aesthetics.
Keywords: Graphic arts -- History -- 20th century; Prints -- Technique; Art and technology